2008
DOI: 10.1055/s-2008-1078407
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Organocatalyzed Interconversion of Silyl Ethers to Tosylates Using DBU and p-Toluenesulfonyl Fluoride

Abstract: A mild and efficient interconversion from silyl ethers to sulfonates esters is reported with good yields. This silyl-sulfonyl exchange proceeds readily in acetonitrile at room temperature in the presence of p-toluenesulfonyl fluoride and a catalytic amount of 1,8-diazabicyclo[5.4.0]undec-7ene (DBU). This method can be used with trimethysilyl (TMS), triethylsilyl (TES) and tert-butyldimethylsilyl (TBDMS) ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
110
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 1 publication
4
110
1
1
Order By: Relevance
“…1), producing aryl sulfonates. [10] We in turn found that fluorosulfates react with aryl silyl ethers under similar conditions, forming diorganosulfates (eq. 2).…”
mentioning
confidence: 99%
“…1), producing aryl sulfonates. [10] We in turn found that fluorosulfates react with aryl silyl ethers under similar conditions, forming diorganosulfates (eq. 2).…”
mentioning
confidence: 99%
“…In this work, we exploited the exquisite reactivity of the sulfur(VI) fluoride moiety toward aryl silyl ethers, a facet of sulfur fluoride exchange (SuFEx) chemistry that was first reported by Gembus 19 and further developed by Sharpless and our laboratories eq 1 and 2. 20,21 SuFEx was also recently exploited for the postmodification of polymer brushes on surfaces, 22 work highly related and complementary to our own herein.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, the S VI eF group can be specifically reacted with certain functional groups (e.g. silane, secondary amine) to eliminate the fluorine while forming a stable sulfuryl linkage (eSO 2 e) between the two components [36,38,39], which demonstrates the potential of using these reactions in linking chemistry. These SuFEx reactions have been demonstrated to be orthogonal, metal-catalyst-free, efficient (i.e.…”
Section: Introductionmentioning
confidence: 99%